2012
DOI: 10.1590/s0103-50532012000100018
|View full text |Cite
|
Sign up to set email alerts
|

Total synthesis and allelopathic activity of cytosporones A-C

Abstract: A busca por herbicidas eficientes e ambientalmente corretos tem sido foco de numerosos estudos sobre a síntese de compostos isolados de fontes naturais. Citosporonas, as quais são lipídeos fenólicos isolados de fungos, apresentam notáveis propriedades biológicas. Este artigo relata a preparação das citosporonas A, B e C, através de uma rota sintética curta e com excelentes rendimentos. Os compostos sintetizados foram avaliados quanto às suas atividades alelopáticas em sementes de alface (Lactuca sativa L). Cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
0
9
0
2
Order By: Relevance
“…Agonist binding to the receptor leads to the activation of receptor-related specific genes that control apoptosis and metabolic regulation [ 41 ]. According to Liu [ 14 ], the pharmacophoric components necessary for binding to Nur77 include the hydroxybenzene ring and the hydrophobic acyl chain, whereas the key element for the activation of the biological function of Nur77 is an ester group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Agonist binding to the receptor leads to the activation of receptor-related specific genes that control apoptosis and metabolic regulation [ 41 ]. According to Liu [ 14 ], the pharmacophoric components necessary for binding to Nur77 include the hydroxybenzene ring and the hydrophobic acyl chain, whereas the key element for the activation of the biological function of Nur77 is an ester group.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is characterized by cell shrinkage, chromatin condensation, and the activation of specific cysteine proteases, known as caspases [ 1 ]. Other authors have demonstrated the apoptotic activity of compounds similar to AMS049 [ 2 , 14 , 16 , 41 , 52 54 ], suggesting the induction of apoptosis by the activation of Nur77 [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dong 等 [12] 利用铑催化的乙烯基氢酰化反应, 从已知化 合物出发经过 3 步以 50.2%的收率得到 Csn-B. 我们前 期的路线 [4] 和 Beatriz 课题组 [13] [14,15] . Willgerodt-Kindler 重 排反应由于操作简便, 而且可以进行克级甚至公斤级的 制备而广泛应用于医药工业 [16] 9), 在该过 程中吗啡啉既是反应试剂又是反应溶剂.…”
unclassified